The Phenomenon of Cultural Genocide: History and Modernity - M. E. Babayan (Евразийская интеграция: экономика, право, политика, 2020)
The article is dedicated to the study of the «cultural genocide» concept as one of the forms of the genocide crime in order to establish the content of culture as the object of the genocide crime. For this, the historical legal method and the method of case study were used (in particular the practice of destroying the culture of the peoples of the Ottoman Empire. Sri Lanka and Tibet for comparison with the possibility of designating them as a crime of cultural genocide, acting as an element of the genocide crime, or as a separate crime with a meaning different from physical and biological genocide). It is concluded that cultural genocide is not a new component of the genocide crime, but an integral part of genocidal policy, and may constitute the phases of pregenocide or postgenocide or act as a separate crime requiring early warning and suppression.